Healing or Haunting : Mourning and Melancholia in the Characters of Haruki Murakami’s Norwegian Wood - Safitri Zona Syardani; Imas Istiani (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study explores the psychological responses to loss experienced by the main characters, Toru and Naoko, in Haruki Murakami's Norwegian Wood (1987). Employing Sigmund Freud's psychoanalytic framework Mourning and Melancholia, this study exhibits how each character demonstrates distinct responses to loss. The study was done using qualitative methodology. The findings shows Toru exemplifies the mourning process, gradually letting go of his attachment to what he has lost and re-engaging with life. In contrast, Naoko portrays characteristics of melancholia through her withdrawal, feelings of guilt, and profound connection to the lost individual, which ultimately leads her to emotional devastation. The study concludes that the novel portrays mourning and melancholia not merely as emotional reactions but as deep contemplations on human identity, attachment, and the human struggle with grief.